Emerging Trends in Fruit and Vegetable Science: Advances in Cultivation, Postharvest Management, and Value Addition - Neelesh Kumar Maurya (International Journal of Trends in Horticulture, 2026)
Fruit and vegetable industries are undergoing a radical restructuring as a result of technological development, sustained focus on sustainable development, and rising customer preferences. This review focuses on the latest changes and developments in cultivation, postharvest, value-addition, and management in the global landscape of horticulture. With a global cultivation of 367.72 million tons and a combined market value of greater than 800 billion USD, the sector grapples with significant challenges; as much as 40% postharvest losses, climate change, and the need for sustainable intensification. This review focuses on trends, such as: precision and smart agriculture, controlled environment agriculture (CEA), use of artificial intelligence, postharvest innovations, and new approaches in value-addition technologies. This review also focuses on innovations, such as vertical farming, hydroponics, and the use of nanotechnology for edible coatings, pulsed electric field, and circular bio-economy. The result of the review has been organized in the form of five detailed tables that represent the comparative analysis of cultivation systems, postharvest technologies, preservation, value-addition, and quality control systems. The synthesis shows that primary postharvest losses can be addressed through some optimally integrated technologies. Repeating this process can also yield better results with how reservations and resources are used, be more time-efficient, and cost-efficient, with a 70–98% efficiency. They can also make products more marketable through extended shelf-lives, whereby shelf lives can be extended by 50–300%. Future research on this emerging field can provide greater clarity for practitioners and policy makers on the road to achieving greater evidence-based synergies for sustainable intensification in the vegetable and fruit sector of the economy, with an increased focus on the intersection of digital technologies, the latest biotechnologies, and principles of the circular economy as the cornerstone of future systems in the fruit and vegetable sector of the economy.
Keywords: Precision agriculture; artificial intelligence; nanotechnology; postharvest technologies; sustainable horticulture; value addition